Pelatihan Kreatif Bahasa Inggris : Membuat Tote Bag Ecoprint untuk Anak SD Negeri Plempukan Ambal Kebumen - Basuki Basuki; Bagiya Bagiya; Ari Fajar Isbakhi; Hendi Arya Pratama; Rizky El Saputra (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to improve the creativity and English language skills of students at Plempukan Elementary School, Kembaran, Ambal, Kebumen through Ecoprint tote bag making training. The method used includes three stages, namely preparation, implementation, and evaluation. In the preparation stage, the team compiled a contextual learning module and prepared natural materials for Ecoprint. The implementation stage began with an introduction to relevant English vocabulary, followed by direct practice in making tote bags with the guidance of a facilitator. Evaluation was carried out through assessment of work results and joint reflection. The results of the activity showed that students were able to master basic Ecoprint techniques, understand and use English vocabulary contextually, and show increased self-confidence and active participation in activities. This activity proves that learning based on creative practice can be an effective medium in improving language competence and art skills in an integrated manner.